Studies on waterline corrosion processes and corrosion product characteristics of carbon steel in 3.5 wt% NaCl solution. Issue 4 (21st October 2020) - Li, Chuanpeng; Zhang, Lunwu; Lu, Zhonghai; Ding, Rui; Zhao, Xiaodong; Wang, Bin; Cui, Hongtao; Liu, Jie
Abstract: The waterline corrosion behaviors of carbon steel partially immersed in a 3.5 wt% NaCl solution were investigated using the wire beam electrode technique, and the effects of corrosion products on the processes of waterline corrosion were analyzed. The results demonstrated that the initial stage and development stage of waterline corrosion were mainly controlled by the concentration and diffusion of dissolved oxygen, respectively, and the deceleration stage of waterline corrosion was mainly affected by corrosion products. The main component of the yellow corrosion products was γ‐FeOOH, and γ‐FeOOH that exhibited a high reduction reactivity could be involved in the cathodic reaction. The black corrosion products were mainly composed of Fe3 O4 with strong thermodynamic stability and the processes of dissolved oxygen diffusion and ion transports were obviously affected due to the continuous accumulation of Fe3 O4 on the surface of the electrodes. Polarity reversals were observed on the single electrodes below the waterline, but the reasons for the phenomena were different from each other. Abstract : The waterline corrosion behaviors and corrosion product characteristics of carbon steel have been analyzed in this study. The waterline corrosion processes of carbon steel could be divided into three stages. The waterline corrosion processes of carbon steel will be greatly affected by corrosion products. Polarity reversals are observed on the single electrodes below the waterline, but the reasons for the phenomena were different from each other.